COMPARISON STUDY ON LIGHT STRUCTURE MODAL PARAMETER USING EXPERIMENTAL MODAL ANALYSIS METHOD VIA PIEZOFILM SENSOR (Jurnal Teknologi (Sciences & Engineering), 2018)
This study determines the effect of modal parameters namely natural frequencies and mode shapes of aluminum 6061 (Al6061)through free dynamic vibration analysis and testing. The simulation procedures was conducted via ANSYS software while the experimental work was performed through impact hammer testing. Three types of specimens in the form  of circular, square and triangular- shapes were used to determine the vibration parameters. Two sensors i.e. piezoelectric film and accelerometer were used. The results for circular shape were ya = 270.55x – 134.82 (accelerometer) and yp = 280.89x – 215.05 (piezofilm);  for square shape were ya = 316.42x – 104.13 (accelerometer) and yp = 309.63x – 43.20 (piezofilm); and for triangular shape were ya = 329.77x – 142.87 (accelerometer) and yp = 305x + 15 (piezofilm). The ya (accelerometer) and yp (piezofilm) are represented as a linear equation of which the data were plotted in mode shape versus natural frequency graph accordingly. By applying the simultaneous equation, the regression ratio can be obtained. The relation between natural frequency and mode shape of accelerometer and piezofilm for the circular-shaped specimen was ya = 0.96yp + 72.3; square-shaped specimen was ya = 1.02yp – 59.98; and triangle-shaped specimen was ya = 1.08yp – 159.08 respectively. The results for the natural frequency from the experimental test were used to compare with the results from the simulation. It was understood that the regression ratios of 0.96, 1.02 and 1.08 of circular-shaped, square-shaped and triangular-shaped were closed to 1.0. The outcome showed that the piezoelectric film sensor is a potential candidate to be used as an alternative sensor for the accelerometer.